Different immunogenicity but similar antitumor efficacy of two DNA vaccines coding for an antigen secreted in different membrane vesicle‐associated forms. Issue 1 (27th August 2014) - Sedlik, Christine; Vigneron, James; Torrieri‐Dramard, Lea; Pitoiset, Fabien; Denizeau, Jordan; Chesneau, Caroline; de la Rochere, Philippe; Lantz, Olivier; Thery, Clotilde; Bellier, Bertrand
Abstract : The induction of an active immune response to control or eliminate tumours is still an unfulfilled challenge. We focused on plasmid DNA vaccines using an innovative approach whereby the antigen is expressed in association with extracellular vesicles (EVs) to facilitate antigen cross‐presentation and improve induced immunity. Our two groups had independently shown previously that DNA vaccines encoding EV‐associated antigens are more efficient at inducing cytotoxic T‐cell responses than vaccines encoding the non‐EV‐associated antigen. Here, we compared our two approaches to associate the ovalbumin (OVA) antigen to EVs: (a) by fusion to the lipid‐binding domain C1C2 of MFGE8(=lactadherin), which is exposed on the surface of secreted membrane vesicles; and (b) by fusion to retroviral Gag capsid protein, which is incorporated inside membrane‐enclosed virus‐like particles. Plasmids encoding either form of modified OVA were used as DNA‐based vaccines (i.e. injected into mice to allow in vivo expression of the antigen associated to EVs). We show that both DNA vaccines induced, with similar efficiency, OVA‐specific CD8 + T cells and total IgG antibodies. By contrast, each vaccine preferentially stimulated different isotypes of immunoglobulins, and the OVA‐C1C2‐encoding vaccine favoured antigen‐specific CD4 + T lymphocyte induction as compared to the Gag‐OVA vaccine. Nevertheless, both OVA‐C1C2 and Gag‐OVA vaccines efficiently prevented in vivo outgrowth of OVA‐expressing tumours and reduced tumour progression when administered to tumour‐bearing mice, although with variable efficacies depending on the tumour models. DNA vaccines encoding EV‐associated antigens are thus promising immunotherapy tools in cancer but also potentially other diseases.